DEVELOPMENT OF CROSS-CULTURAL SKILLS THROUGH THE CASE METHOD: PROBLEM STATEMENT (Intent Research Scientific Journal, 2023)
The paper considers the possibility of using the case method as an innovative technology in the development of intercultural skills in secondary school. The use of the case method in foreign language classes involves several goals: the development of intercultural communicative competence, as well as the development of critical thinking among students. The advantages of this method are considered, as well as the conditions necessary for the implementation of the case method in the process of teaching a foreign language. The problem of developing practical methods of introducing the case method into the educational process in order to develop students' intercultural skills is investigated. Several author's cases have been developed and presented, and the procedure for organizing training using the case method is described.